The Legal and Regulatory Environment of Business - O.Lee Reed (Mc Graw Hill Irwin, 2005)
Now in its ninth edition, this US business law text contains coverage of both the legal and regulatory environment of business, actively preparing students for decision making. The concepts and applications or regulation to various aspects of business, for example employment practices and marketing are emphasized, and six chapters of "traditional" business law (part II), including contract, torts, and liabilities, are included. This edition contains a new chapter on ethics (ch.11), which recognizes the fact that self regulation probably has a great impact on business conduct as does regulation by government, and a new chapter on criminal law and business (ch.8), covering the subject of white-collar crime which is of growing importance to society in general and business in particular. Chapter 10 has been revised, bringing the topic of international law up-to-date, and the realistic new "Typical business decisions" previews at the beginning of each chapter illustrate the relevancy of the topics covered to daily business experiences.